PROGRAM FOR THE ANALYSIS OF PLANE TRUSSES - Makunza, John K. (Tanzania Journal of Engineering and Technology, 2018)
The ' TRAP - TRuss Analysis Program ' can assist engineers in the analysis of plane truss-type structures, as well as prove an excellent basis for understanding the "finite €“ element" method. The Program is completely menu-driven, with all nodes, elements, and load data entered through an input file. TRAP includes plotting for displaying the truss geometry in its original shape showing all nodes and support points. In the analysis process, firstly the structure data; e.g number of nodes, elements, materials and supports are to be defined. Secondly, element properties and support constraints have to be specified. Finally, nodal global loads are then defined. The program output include; displacements for each node, axial forces, length of each element and reactions at the supports. The program aims at reducing the time of analysis and increase the accuracy of calculations as well as storage of the analysed data. The program caters for manual methods of truss analysis such as method of sections or joint method. It has been found that the program is efficient and has no limitations on the number of nodes and elements. The program is suitable for use by design engineers in analysing Plane €“ Trusses of any size.